Diode laser surgery for benign prostate hyperplasia: a comparative analysis of the efficacy and safety of two techniques - S. A. Rakhimov; I. V. Feovilov; I. A. Arbuzov (Вестник урологии, 2023)
Introduction. The urgency of the issues evaluating the effectiveness of various laser surgery techniques in patients with benign prostatic hyperplasia (BPH) is determined by the presence of a significant number of various complications.Objective. To conduct a comparative analysis of the efficacy and safety of two methods of diode laser surgery for benign prostate hyperplasia.Materials & methods. Retrospective study by monitoring and analysing histories included 52 patients with BPH to compare the efficacy and safety of two techniques of diode laser surgery of BPH. The surgical intervention (prostate enucleation — DiLep or vaporization — DiVap) was performed using diode laser with power of 150 W and wavelength of 980 nm ("MILON" Ent., St. Petersburg, Russian Federation). The efficacy of laser technologies was evaluated according to the following criteria: surgery time (min), prostate volume (cx), post-void residual urine volume (ml), severity of LUTS and quality of life related to urination according to the IPSS-QoL scale (points).Results. The DiLep time for prostate volume 71.3 ± 20.2 cc was 62 - 95 min (71.3 ± 12.6 min), whereas for prostate volume 70.4 ± 21.3 cc the DiVap duration was 50 – 67 min (59.8 ± 8.6 min) with a significant difference between the groups (p = 0.0001). The mean length of hospital stay for patients in the DiLep group was 3.4 ± 1.2 bed-days, whereas in the DiVap patient group it was significantly shorter and averaged 2.2 ± 1.1 bed-days (p = 0.008).Conclusion. Diode laser vaporization (DiVap) requires significantly less surgery time and length of hospital stay than hyperplasia enucleation (DiLep).